School children’s attitudes toward green education: Validity and reliability of the revised 2-MEV scale in West Bengal, India (Journal of Applied Learning and Teaching, 2025)
Schools are strongly encouraged to transition from traditional didactic teaching methods to smart education to enhance the overall learning experience for students. Over the past 40 years, technological advancements have led to significant breakthroughs in learning. One important initiative, known as green schooling, plays a crucial role in promoting sustainable development by equipping individuals with the necessary knowledge, skills, values, and perspectives to tackle environmental challenges and strive for a more sustainable future. So, here, the attitudes of school children towards green education (GE) are explored by examining environmental utilization (UT) and preservation (PR). This present study aimed to test the validity and reliability of the Revised 2-MEV Scale of Johnson & Manoli (2010) in the Indian context. With a sample size of 222 secondary students from West Bengal, India, this study followed descriptive statistics such as Mean, Median, and Test of normality, Kaiser-Meyer-Olkin (KMO) Test, Bartlett’s Test of Sphericity (BTS), Confirmatory Factor Analysis (CFA) and Cronbach’s Alpha using AMOS v21 and SPSS v23. The original scale with 16 items across two constructs was retained throughout the stringent validation process and resulted in a high-reliability score proving it apt for future usage to measure 16-18-year-old students’ attitudes towards green education. The analysis of responses concerning Environmental UT and PR was two key dimensions, supported by sub-factors. The Goodness of Fit index (GoF) (CMIN/DF=1.654) confirms the appropriateness of the model. The revised 2 MEV scale is a valuable and reliable tool for assessing students’ attitudes toward green education (GE) in West Bengal, India. Researchers, academics, and policymakers may use the scale to understand the attitude of 16-18 aged children towards green education. Stakeholders can utilize this scale to find existing gaps in understanding, raise awareness about environmental issues, and improve the quality of GE training.